Observed air/soil temperature trends in open land and understory of a subtropical mountain forest, SW China. (27th April 2012) - You, Guangyong; Zhang, Yiping; Schaefer, Douglas; Sha, Liqing; Liu, Yuhong; Gong, Hede; Tan, Zhenghong; Lu, Zhiyun; Wu, Chuansheng; Xie, Youneng
Abstract: This study seeks a further understanding on climate trends in a subtropical mountain forest, SW China. Air ( T a ) and soil temperature ( T s ), both in open land (1983–2010) and under a forest canopy (1986–2010), were investigated. Short‐term radiation components were also measured simultaneously both in open land and understory to explore the relationships of microclimatic variables. Correlations of T a and T s with sunshine hours ( S t ) and wind speed ( W s ) were also analysed as driving factors of the temperature trends. The results showed that (1) Understory radiation components were greatly reduced by the forest canopy, showing a strong effect of forest canopy on microclimatic variables. T s _0 in open land was significantly correlated with solar radiation. Wind speed had significant influences on differences between T a and T s _0, between open land T s _0 and understory T s _0. The long‐term data showed that T s _0 under forest canopy were closely coupled with T a in open land. (2) T a had a larger increase than T s _0 in open land, and temperature increases in winter were greater than in other seasons. Soil temperature at depths under forest canopy had nearly twice the increases of those on open land; we attributed this to the higher relative increase of W s over S t . (3) A slope change in 1998 was detected in the T s _0 and T a difference ( T s _0 − T a ) series, suggesting different response of T s _0 and T a since that year. Deceleration of S t and stability of W s may have been factors. This study improves our understanding of warming in a nature reserve where anthropogenic influences are absent. Further studies are needed for the biological and biochemical implications on subtropical mountain forest. Copyright © 2012 Royal Meteorological Society